(untitled) (Research, Society and Development, 2022)
Amputation is characterized as one of the biggest public health aggravating factors, and is directly related to complications from chronic diseases, injuries and/or traumas. In this way, limb amputations are characterized by removal from the affected region, being performed more in emergency procedures. Therefore, knowing the relevance of this theme, the objective of this study is to identify in the literature, scientific evidence about the main care performed by the multiprofessional team to amputees, being carried out through an integrative literature review, carried out through searches in the databases of scientific data: BRISA, SCIELO, LILACS and BDENF. The research problem found concerns that the main assistance provided by the health team encompasses the monitoring and follow-up of this public.